Temporary occupation licence under the national land code 1965 / Hayatul Akmal Hj. Abdul Aziz - Abdul Aziz, Hayatul Akmal (Faculty of Law, 1985)
An area of law which is based on the implementation of the statutory provision certainly requires a detailed study of various cases and see how they were implemented. The writer's interest in the question of implementation of Temporary Occupation Licence was kindled when she first studied about land law in her second year. Basically, the National Land Code is clear on the rights and liabilities of a Temporary Occupation Licence holder. My discussion will therefore be entered primarily on the implementation of the law and in comparison with other types of disposal. As Temporary Occupation Licence is one mode of disposal. My discussion will therefore be centered on the comparison between Temporary Occupation Licence and other modes of disposal. Special focus will be on comparison between alienation and temporary occupation licence.